Intergovernmental Transfers and Decentralised Public Spending - Bergvall, Daniel (OECD Publishing, 2006)
Intergovernmental grants are used in many countries to finance sub-national spending and to implement national policies. However, the governance of grants is complex, and practices vary widely across OECD countries. The aim of this article is to provide a study of grant design that will be useful to policy makers. The article attempts to integrate both theoretical and empirical insights from the fiscal federalism literature as well as information obtained directly from practitioners concerning their experiences with the implementation of different types of grants. A typology of grant is presented, as well as an overview of the purposes of grants. The article concludes with some principles of grant design and implementation issues
Keywords: Taxation